Simultaneous elections for budget efficiency: Advancing fair and inclusive democracy - Yenita, Yenita (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2024)
General elections in Indonesia, a cornerstone of the country's democracy, face significant challenges in the post-COVID-19 era. This research examines the efficiency, implementation, and impact of Law Number 7 of 2017 and Law Number 10 of 2016 in the context of the 2024 simultaneous elections. The study emphasizes financing efficiency, evaluates implementation outcomes, and compares simultaneous and non-simultaneous elections. The research incorporates legal principles grounded in responsive law theory and progressive law theory and employs a descriptive-analytical and qualitative approach. Findings reveal the successful implementation of Law Number 7 of 2017 during the 2019 simultaneous elections, achieving notable efficiency in cost and time savings. However, challenges such as logistical complexities and inaccuracies in voter data management require further attention. The synergy between Law Number 10 of 2016 and Law Number 7 of 2017 provides a robust legal framework, fostering more effective and participatory general elections. The study underscores the importance of the interconnection between election laws and the administration of simultaneous elections in strengthening Indonesia’s democratic processes. Addressing existing challenges and ensuring consistency in regulatory frameworks will be crucial for enhancing the integrity and efficiency of future general elections.